Civil site selection of the gas engine power plant by value-based decision multicriteria in Kupang, Indonesia - Retnaningtias, Agustina Dwi; Arifin, Zainal; Anugia, Zakie (Universitas Mercu Buana, 2024)
Site selection is one of the main activities in technical system planning to achieve the best design and location of the power plant. Improper site selection methods tend to increase the construction cost, create difficulties in securing primary energy sources, and cause inefficient electricity distribution. The earlier civil site selection process using the scoring method adopted by several utility companies still had some disadvantages that required improvement. This study aimed to propose and test a civil site selection method based on the economic Multi-Criteria Decision-Making (MCDM) that combines Geographical Information System (GIS), Analytical Hierarchy Process (AHP) and Value Based Decision (VBD) simultaneously and based on the collaborative assessment of several engineers. The study investigated Kupang GEPP 40 MW with five alternative locations using the Expert Choice 11 tool to determine the weight of the criteria, alternative locations rating, and the weight of the cost estimate based on GIS data. The analysis revealed that only alternative 1 and alternative 5 are considered feasible. Alternative 5, Panaf, emerges as the most favorable site for Kupang GEPP with a value of 7.087. Further research has been suggested to include more detailed data for site selection.